Carboplatin and Paclitaxel as an Initial Treatment in Patients with Stage IV A & IVb Cervical Cancer: A Report of 16 Cases and a Review of the Literature - Amit Rana (Journal of Biomedical and Pharmaceutical Research, 2023)
Objective: Ca Cervix in 2nd most common malignancy in India and worldwide. NACT is not standard treatment  in Advanced  Ca Cervix. In this study we try to see the response rate of P+C NACT  and to see if patients are able to complete definitive RT in advanced CA Cervix pt. Stage IVA and IV B post NACT. Methods: Am bidirectional study to see the demographic profile  and treatment response when patients receive P+C NACT. We reviewed the demographic data and treatment details of patients who has received NACT for advanced Ca Cervix from our prospectively maintained database from 2019 till 2022.Results: Out of 386 number of registered pt. Of ca cervix , 156 number of patients were  of advanced ca cervix malignancy registered in this time period  17number of pt. Received NACT with P+C , median  age of these patients was 52.2( 39-71yrs ) 16% of patients who were planned for NACT received 3.number of cycles. Overall, the treatment of PC  was well tolerated. The overall response rate was 75%.(2 complete response, 10 partial response). Although grade 3-4 hematologic toxicities were observed in 4 out of 16 patients (25%), 3 patients experienced grade 3-4 non-hematologic toxicities,2 neurotoxity ,1 nephrotoxicity. Out of 14 ,who completed NACT and underwent definitive CRT , 8 (57.14 %) achieved complete responseConclusion: PC is having response and efficacy   and well tolerated in patients FIGO stage IVa &  IVb cervical cancer. This combination can  be considered as an initial treatment regimen in locally advanced  cervical cancer  patient population.Key Words: Cervical cancer, Neoadjuvant chemotherapy (NACT), Paclitaxel (P) and cisplatin (C)